THE ROLE OF LIBRARIANS IN IMPROVING COMMUNITY PRODUCTIVITY OF MSME ACTORS AND ACCELERATING DIGITAL LIBRARY TRANSFORMATION IN ACEH - Saiful Bahgia; Hasbi (Lembaga Riset dan Inovasi Kreyat Center, 2023)
The library as a vehicle for lifelong learning develops the potential of the community and educates the nation's life. In accelerating digital transformation to increase the productivity of UMKM actors in Aceh, the role of librarians is needed to be maximized in Aceh. This is because social media is the main source of the public in accessing the various information needed. As the main pioneer in the success of digital libraries, the role of librarians as information providers and services is needed to contribute to the progress of digital libraries in Aceh, especially for UMKM actors to take advantage of their gedget to access various kinds of references in digital libraries (e-Liberary) in developing its business. Librarians here are spearheads in providing digital literacy to the public, to minimize news and information that is hoax, misuse of social media and other cyber access during the pandemic and post-pandemic. The acceleration of Digital Library Transformation is expected to be able to stimulate Indonesia's economic growth, the creation of new jobs and the realization of the implementation of the Job Creation Law on the empowerment, guidance, and protection of UMKM in Indonesia.